Menemukan Ketenangan Hati di Tengah Badai Informasi: Refleksi Tauhid Rububiyah bagi Netizen : Penelitian - Dadan Nurulhaq; Miftahul Fikri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The digital era has ushered humanity into the phenomenon of information overload, which affects not only cognition but also mental health and spiritual stability. Netizens are frequently trapped in digital anxiety caused by social media algorithms,